IMPLEMENTASI MODEL CTL DENGAN MEDIA AUDIO VISUAL UNTUK MENINGKATKAN MOTIVASI DAN PRESTASI BELAJAR IPS SISWA KELAS VIII E SMP NEGERI I KECAMATAN KEDAWUNG KABUPATEN SRAGEN - Ariningtyas, Titik; Joebagyo, Hermanu; Suryani, Nunuk (Sebelas Maret University (UNS), 2014)
The aims of the study to describe : ( 1 ) the application use CTL model with audio-visual media to increase motivation study class VIII E of SMPN 1 kedawung District of Sragen ; ( 2 ) the application of learning model use CTL with audio- visual media to enhance the student’s learning achievement class VIII E of SMPN 1 kedawung District of SragenThis study uses a Class Action Research ( CAR ) is a means to investigate , refine and evaluate learning.The proceses are carried out with 4 stages there are, including planning , implementation , observation and reflection . The fourth of stage are forming a cycle , carried out collaboratively. The subjects of this research is grade VIII E students of SMP Negeri 1 Kedawung. The data comes from students and teachers ,there are the student's motivation and student’s achievement in learning activities. The Data collection techniques is done by observation, interviews, document analysis and tests. This research uses descriptive analysis of data and compares the findings with performance indicators.The results showed that: (1) the application of learning models CTL with audio-visual media in teaching social studies can enhance student motivation class VIII E of SMPN 1 kedawung; (2) the application of learning model use CTL with audio-visual media in learning activity can improve student achievement class VIII E SMPN 1 kedawung. The Increased student motivation can be seen from the results of student motivation questionnaire after implementing the action. in the first cycle reaches 75.87%, then the cycle II reached 82.78% and the third cycle increased to 83.80%). While student achievement on the initial conditions shows that the average value of 73.12 with 71.87% classical completeness, after the action on the first cycle increased the average value becomes 73.12 with classical completeness amounted to 71.87%, second cycle increased with an average value of 75.03 with classical completeness 75%, and the third cycle experienced a significant increase in the average value reached 80.12 by 84.38% classical completeness.